PENGABDIAN MASYARAKAT BERBASIS PENDATAAN PARTISIPATIF DALAM PERCEPATAN REHABILITASI DAN REKONSTRUKSI PASCABENCANA BANJIR DI GAMPONG GLUMPANG PAYONG, KECAMATAN BAKTIYA, KABUPATEN ACEH UTARA - Pangeran Putra Perkasa Alam Nasution; Amiruddin Ketaren; Yuli Santri Isma; Rakhmadsyah Putra Rangkuty; Shira Thani (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The flood disaster that struck Glumpang Payong Village, Baktiya District, North Aceh Regency, in November 2025 caused significant physical damage, economic losses, and disruptions to community activities. These conditions highlighted the need for accurate data to support post-disaster rehabilitation and reconstruction planning. This article aims to describe a community service program employing participatory damage and loss assessment after flooding and to analyze its contribution to community-based recovery governance. The program adopted a participatory and collaborative approach involving university lecturers, students, village officials, and affected residents. Data collection methods included field observations, structured interviews, community-based verification, and documentation of damage conditions. The results indicate that the participatory assessment successfully identified 70 flood-affected households with a data completeness rate of 100 percent. The collected information covered housing conditions, household asset damage, and estimated economic losses experienced by residents. The participatory approach enhanced data validity, transparency, and community engagement in post-disaster recovery planning. In addition to producing a comprehensive database, the program strengthened collaboration among universities, village governments, and local communities in supporting more targeted rehabilitation and reconstruction efforts. Therefore, participatory assessment can be recommended as a community service model for strengthening inclusive, accountable, and sustainable post-disaster recovery governance.